Evaluation of Aggregated Ag85B Antigen for Its Biophysical Properties, Immunogenicity, and Vaccination Potential in a Murine Model of Tuberculosis Infection - Ahmad, Faraz; Zubair, Swaleha; Gupta, Pushpa; Gupta, Umesh Datta; Patel, Rakesh; Owais, Mohammad (Frontiers in Immunology, 2017)
Protein aggregates have been reported to act as a reservoir that can release biologically active, native form of precursor protein. Keeping this fact into consideration, it is tempting to exploit protein aggregate based antigen delivery system as a functional vaccine to expand desirable immunological response in the host. Herein, we explored the capacity of aggregated Ag85B of Mycobacterium tuberculosis to act as a prophylactic vaccine system that releases the precursor antigen in slow and sustained manner. Being particulate system with exposed hydrophobic residues, aggregated Ag85B is likely to be avidly taken up by both phagocytosis as well as fusion with plasma membrane of antigen presenting cells, leading to its direct delivery to their cytosol. Its unique ability to access cytosol of target cells is further evident from the fact that immunization with aggregated Ag85B led to the induction of Th1 dominant immune response along with up-regulated expression of qualitatively superior polyfunctional T cells in the mice. Antibodies generated following immunization with aggregated antigen recognized both native and monomeric Ag85B released from protein aggregate. The implicated immunization strategy offers protection at par to that of established BCG vaccine with desirable central and effector memory responses against subsequent Mtb aerosol challenge. The study highlights the potential of aggregated Ag85B as promising antigen delivery system and paves the way to design better prophylactic regimes against various intracellular pathogens including Mycobacterium tuberculosis.